KAJIAN AVAILABILITAS PADA SISTEM KOMPONEN SERI - Avida Nugraheni C.; Sudarno Sudarno; Triastuti Wuryandari (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2013)
Availability is a measure of system performance and measures the combined effect of reliability, maintenance and logistic support on the operational effectiveness of the system. Availability of series system is derived from inherent availability of system that takes effect from mean time to failure (MTTF) and mean time to repair (MTTR). Given observed time data of microcontroller consists of processor core, memory and programmable I/O peripheral in series, is measured its system availability. By simple linier regression method, the parameter estimation is determined after data distribution known, for the mean time. Processor core has Weibull distribution for failure time data with , and as regression model while repair time data is lognormal distribution with , and regression model is . Memory has exponential failure time data with and as regression model while normal repair time data has dan and regression model is . Failure time data distribution of programmable I/O peripherals is Weibull with , and regression model while lognormal repair time data has , and regression model is . Due to MTTF is 11364.57 hours and MTTR is 41.59 hours, processor core’s availability is 99.64%. Availability of memory is 99.87% from MTTF is 20000 hours and MTTR is 27 hours. Programmable I/O peripheral has 18773.41 hours as MTTF and MTTR is 38.67 hours that deliver availability 99.79%. The series system availability is 99.30% means the probability of system is in the state of functioning at given time is 99.30%.